Strategi Kebijakan Pembangunan Kabupaten Kepahiang (Analisis SWOT) - Azuwandri Azuwandri (UNIVED Press, 2022)
This research focuses on the selection of policy strategy priorities in Kepahiang District in making a right decision to carry out priority scale development, with the method used in this research is to use a SWOT analysis approach. The results of this study concluded that the results of the weighting of the SWOT questionnaire, then the proposed alternative strategies that can be recommended are the Strength - Opportunity (SO) Strategy, a strategy that uses power to take advantage of opportunities with funding support from the central government in the form of transfers, the availability of facilities and economic infrastructure, developing tourism potential, and maintaining Kepahiang District as an agricultural / coffee granary area.